Activities in software project management class: An experience from flipped classrooms - Ramingwong S. (2017)
© Springer Nature Singapore Pte Ltd. 2018. Teaching in 21st century mainly focuses on students. It is debatable that whether traditional lecturing or practical workshop is more efficient. This paper describes results of flipped classrooms on software project management which students were assigned to organize one activity at the end of the semester. The result suggests the students’ preferences as well as ideas for future innovations.